The Existing Of Supportive Technology Tools For Hand Motor-Impaired User: A Systematic Literature Review - Roszali, Farah Farhana; Ahmad, Ibrahim; Salam, Sazilah; Sarudin, Norziah (Seventh Sense Research Group, 2020)
Diabetes Users who encounter physical and motor impairment persist in struggle to archive the target of performance in the form of hand gesture improvement. Hand gestures are allowed people to give a sign as a communicate medium and to hold, grip and pinch the object. The low ability of hands makes the movement or gesture limited and difficult for them to do the routine activity. This review aim to evaluate the effect of whether the existing supportive technology can assist the hand motor-impairment user. A total of 31 papers were identified and only 10 papers were selected in this review. In this paper, the existing supportive technology tools in the field of motor rehabilitation which is focused on hand motor-impaired users are reviewed. The existing of supportive technology for hand motor-impaired user is not a new field as the paper reviewed from 2014 until 2019. There are few innovations or initiatives from the previous research and study that give a positive effect on the users were identified. Future research is needed to further appreciate and improved the desired role of people with hands motor-impaired in meaningful technology development.